AN ANALYSIS IMPLICIT MEANING OF NAGEKEO‘S CULTURAL LANGUAGE - Benisius Pao (Lantern: Journal of Language and Literature, 2026)
This research is descriptive qualitative research, with the title An Analysis the Implicit of Nagekeo’s Cultural Language. Descriptive qualitative research is research that aims to describe in depth and accurately the phenomena, situations, or conditions that exist naturally, without manipulation of variables, and without considering the value of cause and effect. The purpose of this research is to know, introduce and study the implied expressions of local language/Nagekeo language so that it remains sustainable as a local culture and linguistic wealth. The methods used in this research are interviews, observation, and document analysis or library research. In this descriptive qualitative research, the researcher carefully examines the implied meanings of the Nagekeo language and translates them into English so that it can be understood by readers.